2018
DOI: 10.1525/elementa.298
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of sinking particles: Oil effects, recovery and baselines in the Gulf of Mexico, 2010–2015

Abstract: The extensive release of oil during the 2010 Deepwater Horizon spill in the northern Gulf of Mexico perturbed the pelagic ecosystem and associated sinking material. To gauge the recovery and post-spill baseline sources, we measured D We interpret this depletion period, also observed in d 13C data, as caused by the incorporation of naturally seeped oil into sinking particles. Determination of post-spill baselines for these isotopic signatures allows for evaluation of anthropogenic inputs in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…Our data show that the DWH site carried a relatively high load of petrogenic PAHs (compared to our Reference site), likely owing to its close vicinity to the shore and the strong influence by the Mississippi River plume. Comparison of our time series with the sediment trap samples collected during the year following the DWH oil spill (August 2010-October 2011; Yan et al, 2016) suggests that the particle fluxes had not recovered to baseline levels by October 2011 (Chanton et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our data show that the DWH site carried a relatively high load of petrogenic PAHs (compared to our Reference site), likely owing to its close vicinity to the shore and the strong influence by the Mississippi River plume. Comparison of our time series with the sediment trap samples collected during the year following the DWH oil spill (August 2010-October 2011; Yan et al, 2016) suggests that the particle fluxes had not recovered to baseline levels by October 2011 (Chanton et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…However, isotope data also suggest that petrocarbon from the spill was still part of the sinking flux (Chanton et al, 2017).…”
Section: Effect Of Seepage On Particle Fluxmentioning
confidence: 99%
“…Oil residues from the DWHOS have persisted in the deep-pelagic habitat of the GoM longer than anticipated. For example, 4-6 years after the DWHOS as found in the water column and in deep-pelagic fishes (Walker et al, 2017;Chanton et al, 2018;Romero et al, 2018). The potential consequences of the DWHOS on deep-pelagic invertebrates are yet to be determined, as exposure to oil-derived toxic compounds has not been previously studied in invertebrates from the pelagic domain of the GoM.…”
Section: Introductionmentioning
confidence: 99%
“…Stout et al [60] observed considerably less hopane biomarker for DWH oil in surface/near surface sediments collected in 2014 compared to those collected in 2010/2011. Chanton et al [70] observed a recovery in suspended sinking particles three years after the DWH oil spill at sites near the well using Δ 14 C analyses. Rogers et al [71] observed recovery in suspended particulates after four years.…”
Section: Plos Onementioning
confidence: 99%